The Impact of Bifunctional Catalyst Synthesis Method Cu/ZnO/ZrO2/Al2O3-HZSM-5 on Dimethyl Ether Production from CO2 and H2 - Alfiana Adhitasari; Fitria Yulistiani; Tufana Muhallik Jahulan; Fauzan Fadhillah (Department of Chemical Engineering, Politeknik Negeri Bandung, 2024)
Indonesia has initiated a zero-carbon emission plan; one strategy is to replace Liquid Petroleum Gas (LPG) with eco-friendly fuels like Dimethyl Ether (DME). However, high Operational Expenditure (OPEX) for CO2 conversion technology poses a challenge. This research aims to address these techno-economic barriers by examining how catalyst synthesis methods, specifically Ultrasonic (US) and coprecipitation (CP), impact the performance of the bifunctional catalyst Cu/ZnO/Zr/Al2O3 – H+ Zeolite Socony Mobil-5 (CZZA-HZSM-5) in DME synthesis. The catalysts are characterized using the Brunauer-Emmett-Teller (BET) method and tested in a fixed-bed reactor at 240°C and 27.6 bar, followed by a bubble reactor containing methanol. Gas Chromatography-Mass Spectrometry (GC-MS) is used for analysis. The US method produces catalysts with higher surface area, pore volume, and average pore diameter than the CP method, with values of 45.93 m²/g, 0.3822 cc/g, and 1.6646 nm, respectively. Correspondingly, the US catalyst shows higher CO2 conversion and methanol yield, at 13.3% and 59.7%. DME as the final product is undetected in GC-MS analysis, likely due to differences in HZSM5 specifications, high reaction rates, and ΔG values above 1. This study enhances understanding of how catalyst synthesis methods affect CO2 conversion efficiency, crucial for developing sustainable fuel alternatives.